Człowiek — odtwórca czy twórca wartości? Dostojewski, Bierdiajew, Bachtin - Krasucka, Katarzyna (Przegląd Wschodnioeuropejski, 2018)
The Russian philosophy of the 19th and 20th centuries, which had grown out of Dostoyevsky’s output, yields some immensely interesting attempts to describe and resolve problems concerning relationship among God, values, and a man. So, it is necessary first to introduce philosophical thought of the author of The Brothers Karamazov with having regard to the Orthodox inspiration. Afterward, we propose to present the conception of Berdyaev (primarily problem of freedom), in order to analyze the base of The New Middle Ages author’s output. On the basis of Berdyaev’s view is the “liberation” reinterpretation of the relationship of a man to God and values. Bakhtin has become an invaluable investigator of Dostoyevsky’s output, and the author of the original philosophy of the act. Bakhtin’s reflection on Dostoyevsky’s poetics and a new look at ethics give us also some interesting anthropological settlements.